Characterization and inducibility of hsp 70 proteins in the male mouse germ line (The Rockefeller University Press, 1990)
The properties and inducibility of the heat shock protein 70 (hsp 70) gene products were examined during differentiation of mouse testicular cells by one and two-dimensional gel electrophoresis and immunoblotting. Low levels of the 72- and 73-kD heat shock proteins normally found in mouse cell lines were detected in the mouse testis. A novel isoform with a relative molecular mass of 73 kD (called 73T) was also observed, in the presence or absence of heat shock. 73T was shown to be produced by germ cells since it was not detected in testes from mutant mice devoid of germ cells. Furthermore, 73T was found only in adult mouse testicular cells, not in testes from animals that lack meiotic germ cells. 73T was synthesized in enriched cell populations of both meiotic prophase and postmeiotic cells, but was not inducible by in vitro heat shock. In the adult testis, low levels of the bona fide 72-kD heat-inducible (hsp72) were induced in response to elevated temperatures. In contrast, in testes from animals in which only somatic cells and premeiotic germ cells were present, there was a substantial induction of hsp 72. It is suggested that hsp 72 is inducible in the somatic compartment and possibly in the premeiotic germ cells, but not in germ cells which have entered meiosis and which are expressing members of the hsp 70 gene family in a developmentally regulated fashion.